(untitled) (Communications in Computational Physics, 2006)
In this work, we propose a kind of cellular automaton model to simulate the railway traffic which is based on NaSch traffic model. The signaling system adopted in this work is the three-aspect fixed autoblock system. We investigate the space-time diagram of traffic flow using our model. The velocities and headways of trains are discussed. The impact of the time interval of trains on train running is also analyzed. Numerical simulation results demonstrate that our cellular automaton model can successfully reproduce some actual railway traffic phenomena.